SUB-CHRONIC EXPOSURE TO LEACHATE FROM OJOTA, LAGOS IS ASSOCIATED WITH LIVER AND KIDNEY TOXICITY IN RATS (FUDMA JOURNAL OF SCIENCES, 2022)
This study evaluated the toxicity of Leachate from Ojota, Lagos dumpsite on the kidney and liver of male Wistar rats. Forty-five male albino rats weighing 180 Â±5.5 grams were randomly divided into five groups (n=9). Group A rats drank distilled water throughout the experimental period while rats in group B, C, D and E were exposed to 25%, 50%, 75% and 100% leachate via drinking water for 45 days respectively. Daily intake of leachate was measured for each group. On the last day, the animals were fasted 8 hours overnight and blood samples were collected for liver and kidney function tests. Our finding revealed that rats exposed to 25%, 50% and 75% drank more of the leachate. There were marked increase (P
Keywords: Leachate; Toxicity; Lagos; Exposure